TMIC-49. POTASSIUM CHANNEL KIR4.1 AND GLUTAMINE SYNTHETASE ARE DYSREGULATED IN GLIOMA - Schirmer, Lucas (Neuro Oncol, 2017)
The potassium channel KIR4.1 (KCNJ10) and the glutamate catalyzing enzyme glutamine synthetase (GS) are highly expressed in glial cells of the central nervous system. Both glial proteins play important roles in the maintenance of neuronal activity and neurotransmission. Dysfunction of both proteins can result in altered neuronal excitability and may lead to excitotoxicity. We analyzed 35 snap frozen tissue blocks (glioblastoma [GBM], n=22; low grade astrocytoma (LGA), n=8; oligodendroglioma (OG), n=3; oligoastrocytoma, n=2). All glioma samples had a matching tissue specimen from both the tumor core and the adjacent normal-appearing infiltration zone. Molecular subtyping (MGMT, IDH1/2, 1p/19q) was available from tumor specimens. We combined conventional histology and immunohistochemistry with gene expression analysis and western blot. In preliminary analysis, we found downregulation of KIR4.1 and GS in the tumor core of GBM samples as compared to matching infiltration zone tissue of the same patients. In addition, KIR4.1 transcript levels were reduced in GBM core tissue as compared to LGA tumor core. The pan-astroglial protein AQP4 was not different between tumor core and infiltration zone. We observed a tendency that reduced GS transcript levels were associated with increased epileptic activity in GBM patients. In summary, we found that both KIR4.1 and GS were downregulated in tumor core versus infiltration zone tissue. Enhanced neuronal excitability and increased risk for epileptic activity might be associated with lack of KIR4.1 and GS activity.